Effect of Manganese and Potassium Humate on some Vegetative and Yield Parameters of Tomato Plant Lycopersicon esculentum Mill Grown in Plastic House (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Afield experiment was conducted in a plastic house in Al-wattifiyah / Babylon Province during 2016/2017 season , soil texture was Loamy Sand with 3 levels of manganese element (0 , 20 , and  40 mg .L-1) using MnSO4.4H2O, and 4 levels of  potassium humate  (0 , 10 , 20 , and 30 ml.L-1) , and their interaction on some vegetative and yield  parameters of tomato plant Shahira  variety. 4 spraying date among 20 days each, The experiment design was according to RCBD with 3 replicates, means were compared using L.S.D at 0.05 probability level.       The result show, the treatment (40 mg  Mn.L-1) gave significant increases in plant height, total leaf  No. , leaf area , plant dry matter , leaf content from chlorophyll, leaf dry matter percent, inflorescence number per plant , and No. of flowers per  inflorescence, No. of fruit per plant, fruit weight, total yield of plant , and total yield per m2  gave high value was 212.65 cm, 42.7 leaf , 172.6 ds2 , 185.9 gm , 45.03 spad , 11.8 inflorescence , 10.2 flowers , 47.6 fruits , 101.8 g m , 4.880 kg, and 16.252 kg.m2 respectively . While potassium humate  spraying  treatment (30 ml.L-1) gave high value to same parameters above with 226.4 cm , 44.4 leaf , 180.2 ds2 , 196.4 gm , 46.53 spad , 11.8 inflorescence, 10.3 flowers, 51 fruits , 105.5 gm , 5.394 kg , and 17.862 kg.m2respectively . The interaction treatment (40 mgm Mn.L-1  + 30 ml.L-1 potassium humate) gave the highest value of all parameters mentioned  above.